Improving the service quality of cross-border e-commerce: How to understand online consumer reviews from a cultural differences perspective - Han, Linlin; Han, Xu (Frontiers in Psychology, 2023)
Introduction Cross-border e-commerce (CBEC) consumers come from different countries; thus, cultural differences may affect their evaluations and perceptions of service quality. This paper follows Hofstede’s framework as a theoretical anchor to explore how to use online consumer reviews that reflect cultural differences to improve the service quality of CBEC. Methods First, based on a latent Dirichlet allocation model, 14 service quality issues that consumers are concerned about in CBEC were identified. Second, a generalized ordered logistic regression model was explored to analyze the cultural influences on consumer sentiment orientation. Finally, the effect of each cultural dimension on consumer service quality perception in CBEC was evaluated by employing a binary logistic regression model. Results The results showed that consumers paid more attention to the service quality of logistics service, customs efficiency and tariff, shopping experience, and so on. Cultural dimensions significantly impacted consumers’ emotional tendencies. Moreover, cultural dimensions had significant impacts on consumers’ service quality perception (e.g., logistics service, trust in sellers, customs disputes, and cell phone performance). Still, consumers’ quality perceptions of some services (e.g., cell phone functions, items as described, logistics package quality, and gifts) were less affected by cultural dimensions. Discussion Our findings not only provide new perspectives for CBEC consumer behavior studies on quality improvement but also provide practical implications for CBEC enterprises.